2020
DOI: 10.1038/s41419-020-2420-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective degradation of IKKα by autophagy is essential for arsenite-induced cancer cell apoptosis

Abstract: Two catalytic subunits of the IKK complex, IKKα and IKKβ, trigger NF-κB activation as well as NF-κB-independent signaling events under both physiological and pathological conditions. Here we identified the NF-κB-unrelated cytoprotective function of IKKα in promoting autophagy by triggering p53 transactivation and upregulation of its downstream autophagic mediator, DRAM1, in the arsenite-treated hepatoma cells, which responses depended on IKKα kinase activity. Furthermore, IKKα triggered p53/DRAM1-dependent aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…In our previous reports, we demonstrated an NF-κB-independent role for IKKα in inducing cytoprotective autophagy by triggering CHK1-dependent p53 phosphorylation, which mediates the subsequent degradation of IKKα (Tan et al, 2020). In the current study, we further revealed the role of IKKα in coactivating CHK1and p300/CBP-dependent p53 acetylation, which is also involved in autophagy induction and the feedback control of IKKα expression, and, thereby, mediating arsenite cytotoxicity.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…In our previous reports, we demonstrated an NF-κB-independent role for IKKα in inducing cytoprotective autophagy by triggering CHK1-dependent p53 phosphorylation, which mediates the subsequent degradation of IKKα (Tan et al, 2020). In the current study, we further revealed the role of IKKα in coactivating CHK1and p300/CBP-dependent p53 acetylation, which is also involved in autophagy induction and the feedback control of IKKα expression, and, thereby, mediating arsenite cytotoxicity.…”
Section: Introductionsupporting
confidence: 68%
“…Next, we examined whether p53 transactivation was also regulated by p300/CBP-dependent p53 acetylation. To this end, p300 and CBP siRNAs were separately introduced into HepG2 cells stably transfected with a p53 luciferase reporter (Tan et al, 2020). Here, we found that upregulation of p53-dependent luciferase activity was also significantly inhibited by knocking down p300 or CBP expression (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…In response to starvation-induced apoptosis and autophagy, DRAM-induced mitophagy or autophagy contributes to apoptosis in hepatocellular carcinoma and breast cancer 27 , 28 . DRAM1 mediated autophagy can degrade IKKα to aggravate arsenite-induced cytotoxicity 29 . However, DRAM1 is also beneficial to cancer.…”
Section: Discussionmentioning
confidence: 99%